A model for rising bubbles interacting with crossflowing liquid. (November 2018) - Aliyu, Aliyu M.; Seo, Hyunduk; Xu, Yang; Wang, Jin-Jun; Kim, Kyung Chun
Highlights: A dynamic model is written for submerged bubbles interacting with liquid crossflow. Correlations for drag coefficient and bubble expansion used closure relationships. Experimental data provided initial conditions as well as validation for model solutions. Predicted rise velocities closely agree with the experimental values. Bubble trajectories well predicted especially at low to medium crossflow velocities. Abstract: The effect of liquid crossflow on the behaviour of submerged bubbles was examined using a theoretical time-varying model based on the equations of motion in two-dimensional space. The results were compared with experimental rise velocities and previously obtained trajectories. Bubble images were recorded using high-speed photography at gas flow rates of 2–25 L/min and crossflow velocities of 0.059–0.334 m/s, respectively. Image processing was then used to measure the bubble rise velocities. Increasing the crossflows strongly limits the bubble rise velocities, which depend on the bubble size, especially at high crossflow velocities. The model's predicted velocities show good agreement with the experimental data, which had uncertainties of around ±10%. The model predicted nearly linear trajectories, which were visually similar to the experimental trajectories. We compared the model's trajectories with swarm centroids and predictions by an empirical correlation developed earlier for the swarm inclination angle. The model's results compared favourably with the experiments, although there were slight overpredictions, especially at high crossflows. This could be corrected in future works by developing more appropriate closure relationships related to crossflows. Graphical abstract: